The Human Being as a Creator of (in) Human Life: The Example of Mary Shelley’s Frankenstein; or, the Modern Prometheus - Rédei, Anna C. (Frontiers in Human Dynamics, 2022)
Humans have an inquiring mind. Throughout history one may find documentation that shows on human curiosity and our drive to stretch boundaries to satisfy it. Thus, this is not something that characterises our time in any particular way. Sources, for instance, from the 13th century can serve as good examples that support such an assumption. Mary Shelley’s novel from the 19th century, Frankenstein, or the modern Prometheus, might perhaps be the most known commentary to that boundary stretching, which continues in a slightly new form in the ongoing debate within as well the popular culture as within the scientific community. Shelley’s narrative about Frankenstein the scientist and his Creature has continued to interest the audience. Through adaptations to film the story has reached many new generations cinema goers. However, new interpretations have altered some aspects the original message. Shelley’s conception of the monstruous was more complex than today when parts of the narrative have been downplayed and others upscaled.